The call of the wild - London, Jack (Champaign, Ill. : Project Gutenberg, 1903)
Illustrated handbill for the American Mutoscope and Biograph Co. film production "The Call of the Wild" showing a white woman on her knees appealing to Native man wearing full headdress.
Published in: Many nations: A Library of Congress resource guide for the study of Indian and Alaska native peoples of the United States / edited by Patrick Frazier and the Publishing Office. Washington : Library of Congress, 1996, p. 254.
Keywords: Indians of North America -- Performances & portrayals -- 1900-1910.; Relations between the sexes -- 1900-1910.; Social classes -- 1900-1910.; Prejudice -- 1900-1910.; Film stills -- Reproductions -- 1900-1910.; Handbills -- 1900-1910.; Halftone photomechanical prints -- 1900-1910.